Answer:
Roots for the given polynomial p(x) is x = (2 + √2i) or x = (2 - √2i)
Explanation:
Here, the given polynomial is
![P(x) = x^(2) - 4x + 6 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jnmv3msrxk4ofcqzvb5w07weof4z391wlv.png)
Now, in COMPLETING THE SQUARE there are various steps.
Step (1): HALF THE COEFFICIENT OF x
Here, the coefficient of x = (4) so , the half of 4 = 4/ 2 = 2
Step(2) :Square it ADD IT ON BOTH SIDES OF EQUATION
The square of 2 is
.
Adding it on both sides of the polynomial, we get
![P(x) : x^(2) - 4x + 6 + (2)^2 = 0 + (2)^2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/livs4qmtusokbifau8emrgzkn0tzsi3zwc.png)
Step (3): Use the ALGEBRAIC IDENTITY and make a complete square.
Now, using the identity
![(a\pm b)^2 = a^2 + b^2 \pm 2ab](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2u923y3lphk4to7cmojk6bw3tp5dazns23.png)
![\implies x^(2) - 4x + 6 + (2)^2 = 0 + (2)^2\\= (x^(2) - 4x + (2)^2 )+ 6 = 0 + (2)^2\\= (x-2)^2 + 6 - (2)^2 = 0\\\implies (x-2)^2 + 2 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mq9vfa3haoifloxr39bn5mzvs51b92m4n6.png)
or,
![(x-2)^2 = -2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kg8jz3zy3pj9c40iith7fbk1y0tge7bj5u.png)
Rooting both sides, we get
![\pm (x-2) = (\sqrt2i)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yowt85zcf7henb5bindrbkutgin35z8fmn.png)
Solving this, further,we get
x = 2 + √2i , or x = x = 2 - √2i
Hence, roots for the given polynomial p(x) is x = 2 + √2i or x = 2 - √2i